Assessing the Primacy of Human Amygdala-Inferotemporal Emotional Scene Discrimination with Rapid Whole-Brain fMRI. (15th May 2019) - Sabatinelli, Dean; Frank, David W.
Abstract: The comparative roles of the human amygdala and orbitofrontal cortex in emotional processing are under substantial debate, supported prominently by invasive primate studies. Noninvasive studies in humans are restricted by the limitations of electro- and magneto-encephalographic methods, which are hampered by the closed-field architecture and deep location of these structures. Here we employ whole-brain functional magnetic resonance imaging at an effective sampling rate of 300 ms to define the latency of enhanced blood oxygen level dependent (BOLD) contrast within structures activated by emotionally evocative relative to neutral scenes, in an effort to assess the hypothesized primacy of amygdala-inferotemporal co-activity in human emotional perception, relative to orbitofrontal cortex. Consistent with much prior work, we identified heightened BOLD signal during pleasant and unpleasant scene presentations in extrastriate occipital, ventral temporal, and posterior parietal visual system, as well as enhanced activation in cortical regions including the dorsal frontoparietal network, insula, and orbitofrontal cortex. Subcortical structures including the amygdala, locus coeruleus, and basal forebrain also showed reliably increased activity during emotional scene perception. The latency at which emotional BOLD signal enhancement varied considerably across structures, ranging from 2 to 6 seconds after scene onset. Though coarse, the spatiotemporal pattern of emotion-enhanced activity identified here is consistent with the idea that the amygdala and inferior temporal fusiform gyrus are the first regions to discriminate scene emotionality, which may then distribute this categorical information to other cortical and subcortical structures. Highlights: Evaluate the primacy of amygdala-inferotemporal activity in emotional scene perception Novel whole-brain functional imaging at an effective sampling rate of 300 ms Amygdala and fusiform gyrus BOLD signal initiate the discrimination of scene emotion